Pengaruh Dosis dan Waktu Aplikasi Pupuk SuburIn Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays L. Var saccharata. Sturt) - Patty, Jacob Richard; Ririhena, Rhony Einstein; Hitijahubessy, Fabians J. D. (Fakultas Pertanian, Universitas Pattimura, 2024)
Sweet corn is the most important, especially to food consumption. This plant is more than consumption as a human and animal which is available in Southeast Molluccan District. This experiment was intended to determine the proper amount of SuburIn and the time they were applied. A Completely Randomized Block Design was used with three replicated. SuburIn was applied in four different amounts including check (D0), 6 g. plant -1 (D1), 12 g plant -1 (D2), 18 g plant -1(D3). These Fertilizer were applied at 7 (day after plant/dap) (W1), 21 dap (W2), and 35 dap (W3). Based on the height of plants, number of leaves, Leaf Area Index, length of ears, diameter of ears, and the fresh weight of ears, best result was gained by the use of 18 g plant-1, applied at 21 dap.